Tourism Guidebooks and the Emergence of Contemporary Tourism in Portugal - Santos, Maria Luísa (2008)
As part of a utilitarian literature, travel guidebooks are a reflection of economic, social, cultural and technological changes that have been introduced, through time, on cultural or summer travels, and have been gradually undertaken by wider and wider social groups. Thus, analysis of various tourist guidebooks allows one to study different topics. On the one hand, travel guidebooks can be connected to the history of art and define the concept of heritage at each point in time. On the other hand, they are connected to the economic history through their interrelationship with different means of transport or new industries, which technological and industrial development provided for the travelers / tourists. Guidebooks act also as a tool for understanding space, which con tributes towards dissemination of information about new leisure facilities, such as spas or beaches, and towards construction of images about cities or the countryside. This chapter focuses on the establishment of the first institution for the promotion of tourism in Portugal and examines some travel guidebooks which were published between the end of the 1 t9I century and the beginning of the t2h0 century.